Pupillometer Use: Validation for Use in Military and Occupational Medical Surveillance and Response to Organophosphate and Chemical Warfare Agent Exposure. Issue 9 (14th March 2018) - Mease, Luke; Sikka, Reema; Rhees, Randall
Abstract: Introduction: To analyze the effectiveness and suitability of pupillometer use in military and occupational medicine, specifically when pupil size is measured as part of medical surveillance. Pupil size is the most sensitive physical exam finding in vapor exposure to substances that inhibit acetylcholinesterase, such as nerve agent (chemical warfare) and organophosphates (used in agriculture). Pupillometer use permits real-time, accurate pupil measurements, which are of significant value in occupational setting where exposure to organophosphates is suspected and in dynamic military settings where it may be unclear if service members were exposed to nerve agent or not. Materials and Methods: In a worker population enrolled in medical surveillance including pupil size measurement, pupils were measured using a Colvard pupillometer, whereas their pupil size had previously been measured by manual measurement. Pupil size was compared pre- and post-pupillometer implementation. Results: Pupil size range was broader post-pupillometer implementation, reflecting accepted ranges of physiologically normal pupil sizes. The correlation between pupil sizes pre- and post-pupillometer was low, and the overall mean pupil diameters were statistically different between the two modalities ( p < 0.0001), strongly suggesting that pupillometer use helped correct inaccurate pupil size estimates. In two real-world situations, pupillometer use proved helpful in evaluating workers who may have been exposed to an organophosphate, providing information that was immediately available and clinically relevant as part of the initial medical evaluation/physical exam. Conclusions: Pupillometer use is feasible and robustly increases the precision and accuracy of pupil size measurement in military and occupational medicine settings caring for workers potentially exposed to organophosphates. It provides near-real-time quantitative data that are immediately pertinent to determining if a service member or employee has been exposed to these agents.